The Effect of Negative and Positive Emotionality on Associative Memory: An fMRI Study - Okada, Go; Okamoto, Yasumasa; Kunisato, Yoshihiko; Aoyama, Shiori; Nishiyama, Yoshiko; Yoshimura, Shinpei; Onoda, Keiichi; Toki, Shigeru; Yamashita, Hidehisa; Yamawaki, Shigeto (PLOS ONE, 2011)
In general, emotion is known to enhance memory processes. However, the effect of emotion on associative memory and the underling neural mechanisms remains largely unexplored. In this study, we explored brain activation during an associative memory task that involved the encoding and retrieval of word and face pairs. The word and face pairs consisted of either negative or positive words with neutral faces. Significant hippocampal activation was observed during both encoding and retrieval, regardless of whether the word was negative or positive. Negative and positive emotionality differentially affected the hemodynamic responses to encoding and retrieval in the amygdala, with increased responses during encoding negative word and face pairs. Furthermore, activation of the amygdala during encoding of negative word and neutral face pairs was inversely correlated with subsequent memory retrieval. These findings suggest that activation of the amygdala induced by negative emotion during encoding may disrupt associative memory performance.